The Integration of Sufism in Contemporary Indonesian Islam: The Case of Urban and Rural Communities - Wijaya Wijaya; Abdillah Rofiif Fatin Ritonga; Amin Zaki; Ahmed Hossam (Islamic Studies in the World, 2025)
Background. Sufism has historically played a central role in shaping Islamic spirituality in Indonesia, yet its presence and function in contemporary contexts—particularly among urban and rural communities—remain underexplored. Amid the dynamic religious landscape of modern Indonesia, marked by increasing pluralism, conservatism, and digital religiosity, the integration of Sufi practices and values continues to adapt and evolve in nuanced ways. Purpose. This study aims to examine how Sufism is practiced, perceived, and institutionalized within both urban and rural Muslim communities in Indonesia. The research investigates the social, spiritual, and cultural factors that influence the persistence and transformation of Sufi traditions in the context of modern life. Method. Employing a qualitative comparative approach, the study conducted fieldwork in two locations: a metropolitan city (Jakarta) and a rural district in Central Java. Data were collected through in-depth interviews with 30 participants including religious leaders, followers of various tariqas (Sufi orders), and community members, supported by participant observation and document analysis. Results. Findings reveal that urban Sufi communities emphasize symbolic spirituality, self-development, and integration with digital platforms, while rural counterparts maintain traditional rituals, communal dhikr, and strong lineage-based networks. Despite contextual differences, both settings reflect a shared commitment to inner transformation and ethical living, with Sufism offering a counterbalance to materialism and ideological rigidity. Conclusion. The study concludes that Sufism continues to serve as a meaningful spiritual resource in Indonesian Islam, adapting to socio-cultural shifts while maintaining its core emphasis on personal piety and social harmony.